Dakwah Inklusif Nurcholish Madjid - Fikri Zuhriyah., Luluk (Jurnal Komunikasi Islam, 2012)
Nurcholish Madjid is synonymous with inclusive Islam discourse. His works are quite consistent in voicing the idea of Islam as an open religion. This article specifically examines the construction of inclusive proselytizing of Nurcholish Madjid and its significance for religious practice. This paper also argues that the people of Indonesia need to embrace and implement inclusive proselytizing in order to create interfaith community or inter-religious harmonyKeywords: Nurcholish Madjid, inclusive proselytizing, inter-religious harmony------------------------------------------------------------------------Wacana Islam inklusif sangat melekat dengan sosok Nurcholish Madjid. Karya-karyanya cukup konsisten dalam menyuarakan gagasan Islam sebagai agama terbuka. Artikel ini membahas secara khusus konstruksi dakwah inklusif Nurcholish Madjid dan signifikansinya dalam konteks keberagamaan. Tulisan ini berargumen bahwa dakwah inklusif perlu digerakkan oleh bangsa Indonesia agar kerukunan antarwarga dan antarumat beragama dapat tercipta dengan baik.Kata kunci: Nurcholish Madjid, dakwah inklusif, kerukunan beragama